PENGARUH KUALITAS PELAYANAN (SERVICE QUALITY) TERHADAP KEPUASAN PELANGGAN PT. SUCOFINDO BATAM - Alfi Syahri Lubis; Nur Rahmah Andayani (Politeknik Negeri Batam, 2017)
This study aims to determine and analyze the influence of service quality consisting of variable reliablility, responsiveness, assurance, empathy, and tangible to customer satisfaction PT. Sucofindo Batam simultaneously or partially. Population in this research is consumer of PT. Sucofindo Batam or consumers who have ever used the services of PT. Sucofindo Batam. The number of samples obtained using Slovin calculations A total of 80 respondents using Non Probability Sampling method. The method of analysis used in this study is descriptive analysis and multiple regression analysis using SPSS 20 program. From the results of the study showed that the persial and simultaneous positive and significant impact on customer satisfaction PT. Sucofindo Batam.